POLA ARGUMENTASI PADA GENRE TEKS EKSPOSISI KARANGAN SISWA SMA - Nurul Khairani Abduh; Andoyo Sastromiharjo; Dadang S. Anshori (Universitas Negeri Makassar, 2019)
Argumentation Pattern on Genres of Exposition Texts by High School Students. This article aims to describe the pattern of argumentation in the essays of student expositions based on the theoretical study of Toulmin's Argumentation Pattern (TAP). The documentation technique was used in data collection in sources in the form of expositions of class X students from five schools in Makassar City, namely Makassar 14 High School (24 data), Makassar 4 Public High School, Makassar 9 Public High School, Athirah Makassar Islamic High School, and SMA Tri Tunggal 45 Makassar. The results of the analysis show nine argumentation patterns produced in the exposition essay, ranging from the most basic and simple patterns to the most complex patterns, namely (1) C-D, (2) C-D-W, (3) C-D-Q, (4) C-D-R, (5) C-D-W-B, (6) C-D-W-Q, (7) C-D-W-R, (8) C-D-Q-R, and (9) C-D-W-B-Q.